2019
DOI: 10.3390/nu11061429
|View full text |Cite
|
Sign up to set email alerts
|

Does Beef Protein Supplementation Improve Body Composition and Exercise Performance? A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Protein supplementation might improve body composition and exercise performance. Supplements containing whey protein (WP) have received the most attention, but other protein sources such as beef protein (BP) are gaining popularity. We conducted a systematic review and meta-analysis of randomized controlled trials that compared the effects of exercise training combined with BP, WP or no protein supplementation (NP), on body composition or exercise performance. Secondary endpoints included intervention effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
(129 reference statements)
0
30
0
Order By: Relevance
“…To our knowledge, this is the first meta-analysis that compares RT plus PS with RT alone or plus placebo supplementation in a healthy elderly population. Notably, there are similar previous studies that compared different populations, such as a younger population [45,46] or elderly hospitalized people [47]; included a combination of other supplements, such as vitamin 3, omega-3, or a dietary intake modification [19,[48][49][50][51]; or studied other outcomes related to body composition [52,53].…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, this is the first meta-analysis that compares RT plus PS with RT alone or plus placebo supplementation in a healthy elderly population. Notably, there are similar previous studies that compared different populations, such as a younger population [45,46] or elderly hospitalized people [47]; included a combination of other supplements, such as vitamin 3, omega-3, or a dietary intake modification [19,[48][49][50][51]; or studied other outcomes related to body composition [52,53].…”
Section: Discussionmentioning
confidence: 90%
“…Of all protein sources and supplements for muscle health, dairy products, and isolated dairy proteins have gained the most attention [ 65 ]. In this review, non-liquid dairy (yogurt and cheese) as a source of high-quality protein, especially whey, have been used in relation to muscle mass, function, and sarcopenia in five studies with healthy and sarcopenic older adults [ 37 , 38 , 39 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…When considering the best protein whole foods for lean muscle mass and function, aside from protein quantity, protein quality (e.g., digestibility/absorption rate to elicit MPS; protein quality scores) continues to be debated in light of muscle physiological outcomes, sustainability, and acceptability in older adults. Regarding physiological outcomes, a recent meta-analysis of studies including younger and older adults has shown no differences between animal protein (beef) versus dairy (whey) supplementation in increasing protein intake and lean tissue mass post-exercise [ 65 ]. Plant (e.g., pea and soy product) versus animal protein foods (e.g., dairy (whey)) have shown comparable effects on several muscle-related outcomes, including muscle thickness, force production [ 70 ], muscle size, strength [ 44 ], and power [ 45 ] in young and older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Meat, as a high-quality protein source, supports muscle protein synthesis and, correspondingly, has the capacity to improve quality of life through improving lean body mass and physical performance [18,19]. However, there has been considerable recent attention on the possible health consequences of a diet rich in red meat, including beef [20,21], yet surprisingly little is known about beef digestion.…”
Section: Discussionmentioning
confidence: 99%